The free market existentialist : capitalism without consumerism - Irwin, William, 1970- (Hoboken : Wiley Blackwell, 2015)
Incisive and engaging, The Free Market Existentialist proposes a new philosophy that is a synthesis of existentialism, amoralism, and libertarianism. -Argues that Sartre's existentialism fits better with capitalism than with Marxism -Serves as a rallying cry for a new alternative, a minimal state funded by an equal tax -Confronts the "final delusion" of metaphysical morality, and proposes that we have nothing to fear from an amoral world -Begins an essential conversation for the 21st century for students, scholars, and armchair philosophers alike with clear, accessible discussions of a range of topics across philosophy including atheism, evolutionary theory, and ethics.
Philosophies of individualism -- Out, out, brief candle!?: what do you mean by existentialism? -- Like cigarettes and existentialism: why there is no necessary connection between Marxism and Sartre -- To consume or not to consume?: how existentialism helps capitalism -- Why nothing is wrong: moral anti-realism -- Not going to hell in a handbasket: existentialism and a world without morality -- What's mine is mine: moral anti-realism and property rights -- Who's afraid of the free market?: moral anti-realism and the minimal state -- Not your father's existentialism.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Existentialism; Free enterprise; Capitalism; Consumption (Economics); Anti-realism.; PHILOSOPHY -- Criticism; PHILOSOPHY -- Movements -- Critical Theory; PHILOSOPHY -- Movements -- Existentialism; Anti-realism.; Capitalism; Consumption (Economics); Existentialism; Free enterprise; Electronic books